Borneo Feeds Enterprise - Ahmad, Abdul Wahab; Ibrahim, Dexter Cysonned; Killi, Noraniza; Sharif Miruddin, Sharifah Normazuana; Mohamad Marzuki, Siti Nurnabilah (2014)
The name of our company is Borneo Feeds Enterprise. Our company sell poultry feed to west coast region in Sabah for example, Kota Kinabalu, Penampang, Tuaran, Sepanggar, Papar and more. We provide services to deliver the feeds to the certain company that want poultry feed. Our main office is located at Makat Industrial Warehouse, Kolombong, Kota Kinabalu Sabah. We are available from Monday to Sunday from 8am to 6pm. We open this business because there is a company that sells poultry feeds but they only sell them with a big company for distributor. If anyone wants to buy from them in a small number, it will take long. Thus, we open this company as a distributor. In order to start this business, we need almost RM400 000 of budget. We also contribute our own assets inside this company.